Diseño e implementación de un sistema de riego por goteo con dosificador de fertilizantes en el área orgánica de la ESPAM-MFL. - Barberán Rodríguez, Marco Antonio (2012)
The present investigative work was carried out in the year 2011, in the organic area of the career of agricultural of the ESPAM `` MFL´´ a watering system was implemented by leak with dosificador of fertilizers in a total area 4828m2 with the following objectives of: To optimize the resource hídrico and the biofertilizantes use in the area of organic cultivations of the Agricultural Career to acquire experience in the watering matter so much in field as theory for the students and farmers of the area. For which was carried out an agronomic and hydraulic design that allows the implementation of the watering system for leak. To be able to determine frequency and watering dose that need the vegetables in general, one had to make physical and chemical studies of the floor to be able to arrive to those results. It was also calculated the pressure and the diameter of the pipe to be able to water certain platabandas numbers for this one had to use you formulate Blasius and of Hazen. In the Implementation of the watering system designed together with the biofertilizantes dosificador. I settle it with the guarantee of the tutor of the watering matter with their respective indications and their respective operation to the like they left in the results for that a regulator of pressure it was admitted to control the differences of pressure that there is in the watering system. As a result I throw that to optimize the resource it dilutes and time to be able to water 21 platabandas a quantity of water 6.56 mm newspapers was needed with a watering interval one hour seven minutes thirty seconds.